Identifying and Analyzing the Key Drivers of the Future of Sustainable Banking Using a Hybrid Approach - Malekpour, Abdolhamid; Jahangirnia, Hossein; Arabi, Seyed Hadi; Pourfakharan, Mohammad Reza (Management Strategies and Engineering Sciences, 2025)
The paradigm of sustainable development and sustainability initially emerged in the industrial sector and supply chains and subsequently extended to the financial sector. Banks play a crucial role in the financial industry, and their sustainability significantly contributes to sustainable development within this sector. The present study aims to identify and prioritize the key drivers shaping the future of sustainable banking in Iran. This research is applied in nature and employs a mixed-methods approach from a methodological perspective. The theoretical population consists of experts and specialists in the banking industry. Sampling was conducted using a judgmental approach based on expertise in the field of sustainable banking. The primary data collection tools used in this study include semi-structured interviews and questionnaires. The research was conducted in three phases. In the first phase, 30 key drivers were identified through expert interviews and thematic analysis. In the second phase, the drivers were screened using expert questionnaires and the fuzzy Delphi method. Eleven drivers with a defuzzified value greater than 0.7 were selected for final prioritization. In the third phase, the screened drivers were ranked using prioritization questionnaires and the CoCoSo method. The highest-priority drivers included: the development of data-driven governance in the country, the models and nature of collaboration between banks, fintech firms, and financial startups, and the movement of banks toward diversifying financing methods. Practical recommendations were developed based on the most significant drivers.